Effect of Cow Manure and Antagonistic Fungus (Trichoderma sp.) on the Intensity of Rhizoctonia solani Kuhn's sheath Blight Attack on Paddy (Oryza sativa) - Melly Farida (Central Research Institute For Agriculture, 2023)
This study aims to determine the effect of fertilizer application cattle pen and antagonistic fungus Trichoderma sp. in suppressing the intensity of attack of R. solani sheath blight on rice plants in greenhouses.pi, and the antagonistic fungus Trichoderma factor. The results of research in the laboratory showed that the macroscopic symptoms of R. solani were initially brownish-white hyphae, then changed to light brown and when the culture was old it would have a dark brown color, while microscopically it was known that this fungus does not have spores, fungal hyphae are insulated, at first transparent white then turns brown, and the branches form elbows. The results of the research in the greenhouse were that the application of cow manure had a significant effect on the attack intensity of R. solani, namely the highest attack intensity was in the treatment without fertilizer (control) of 9.82% and the lowest attack intensity was in treatment 2.5 of 4 .75%, while the administration of antagonistic fungi did not significantly affect the intensity of R. solani attacks, as well as the interaction between the two treatments did not have a significant effect. Symptoms of attack from R. solani in the field are white mycelium, and brownish-gray spots on the leaf midribs close to the soil surface, these spots then expand to form blight, if the attack continues the base of the stem will rot and the leaf sheaths wither.